Cardiovascular risk factors and risk of venous thromboembolism - Brækkan, Sigrid Kufaas (Universitetet i Tromsø, 2010)
The papers of the thesis are not available in Munin, due to publisher's restrictions: 1. Brækkan SK, Mathiesen EB, Njølstad I, Wilsgaard T, Størmer J, Hansen JB: 'Family history of myocardial infarction is an independent risk factor for venous thromboembolism – The Tromsø Study', Journal of Thrombosis and Haemostasis, 2008, Nov; 6(11): 1851–1857 (Wiley-Blackwell). Available at http://dx.doi.org/10.1111/j.1538-7836.2008.03102.x 2. Borch KH, Brækkan SK, Mathiesen EB, Njølstad I, Wilsgaard T, Størmer J, Hansen JB: 'Abdominal obesity is essential for the risk of venous thromboembolism in the metabolic syndrome - the Tromsø study', Journal of Thrombosis and Haemostasis, 2009 May; 7(5): 739-45. Available at http://dx.doi.org/10.1111/j.1538-7836.2008.03234.x 3. Brækkan SK, Borch KH, Mathiesen EB, Njølstad I, Wilsgaard T, Hansen JB: 'HDL-cholesterol and future risk of venous thromboembolism – The Tromsø Study', Journal of Thrombosis and Haemostasis, 2009 Aug; 7(8): 1428-30. Available at http://dx.doi.org/10.1111/j.1538-7836.2009.03481.x 4. Brækkan SK, Mathiesen EB, Njølstad I, Wilsgaard T, Størmer J, Hansen JB: 'Mean platelet volume is an independent risk factor for venous thromboembolism – The Tromsø Study', Journal of Thrombosis and Haemostasis, 2010 Jan; 8(1): 157-162. Available at http://dx.doi.org/10.1111/j.1538-7836.2009.03498.x Venous thromboembolism (VTE), including deep vein thrombosis and pulmonary embolism, is a common disease, with serious short- and long-term complications and a potential fatal outcome. Despite the knowledge of several inherited and acquired risk factors for VTE, still 30-50 % of the VTE events occur in the absence of obvious predisposing factors. Traditionally, arterial and venous thrombosis has been considered as separate disease entities with different pathology, epidemiology and treatments. However, recently this concept has been challenged, and a potential link between arterial cardiovascular disease and VTE has been suggested. The aim of this thesis was to investigate the impact of ...